Induction Heating of Inner Rolling Bearing Ring in ANSYS - Novak, Pavol; Dekys, Vladimir (Manufacturing Technology Journal, 2015)
Aim of this paper is to explain capability of ANSYS to model induction heating of inner rolling bearing ring. This physical problem requires simulation of the interaction of three physical fields. First field is harmonic low-frequency electromagnetic, second transient thermal and third static structural analysis. The skin effect requires the fine mesh in areas near boundary of modeled ring in the vicinity of inductor. MFS concept is used to couple these three physical fields. Main result of this analysis is the thermal field history in inner ring. This analysis is used to obtain sensitivity data for appropriate shape and size of inductor to austenitize required domains of inner ring.
Keywords: Induction heating of inner ring; ANSYS APDL; Thermal field